EFEKTIVITAS DISCOVERY LEARNING METHOD UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PAI DI SMA - Widia Lestari, - (2023)
Critical thinking skills are one of the crucial skills that must be possessed by students to deal with the dynamics of life in the industrial era 4.0 and the era of society 5.0. However, ironically, students' critical thinking skills in Indonesia are still in the bottom 10 rankings based on the PISA report. With this reality, a breakthrough is needed in improving students' critical thinking skills, one of which is by changing learning methods. This study aims to find out how the role of the discovery learning method in improving students' critical thinking skills. This study uses a quantitative design with experimental methods, the aim is to determine changes in critical thinking that occur after using the discovery learning method. Based on the findings, before being given action, more than half of the sample had critical thinking skills in the "Very Low and Low" categories in both the control class and the experimental class. After the researchers carried out the learning process for 7 weeks using the discovery learning method, there was a significant difference in the results of critical thinking skills between the two class groups. In the experimental class, more than half of the students have a category of critical thinking at the "High and Very High" level, with this average increase when compared to the N-Gain percentage value, it can be concluded that the discovery learning method is "Quite Effective" for improving students' critical thinking skills. Keywords: Critical, Method, Discovery